THE INFLUENCE OF THE WORK ENVIRONMENT AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE ENGAGEMENT - Tri Widyaningrum, Kharisma; Noni Setyorini; M. Fadjar Dharmaputra (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to investigate the influence of the work environment and career development on employee performance mediated by employee engagement. The study uses a quantitative approach with a questionnaire as the research instrument. The sample consists of 130 respondents, selected through random sampling from a total population of 175 employees working at Perusahaan Daerah Air Minum Tirta Moedal Kota Semarang. Data were analyzed using Structural Equation Modeling (SEM) with Smart PLS 4 software. The data have met validity and reliability tests, indicating that the results are suitable for hypothesis testing. The findings are as follows: (1) The work environment variable does not affect the performance of PDAM Kota Semarang employees (2) The career development variable has a positive and significant impact on the performance of PDAM Kota Semarang employees (3)The employee engagement variable has a positive and significant impact on the performance of PDAM Kota Semarang employees (4)The work environment variable has a positive and significant effect on employee engagement at PDAM Kota Semarang (5)The career development variable has a positive and significant effect on employee engagement at PDAM Kota Semarang (6)The work environment variable has a positive and significant effect on employee performance at PDAM Kota Semarang, through employee engagement as a mediating variable (7)The career development variable has a positive and significant effect on employee performance at PDAM Kota Semarang through employee engagement as a mediating variable.